Use of Double Myocutaneous Flap after Extended Resection of Locally Advanced Ulcerated Breast Carcinoma - Costa Vieira, Rene Aloisio da [UNESP]; Navarro de Oliveira, Luiz Carlos; Ching, An Wan; Oliveira-Junior, Idam de [UNESP] (Lippincott Williams & Wilkins, 2022)
Locally advanced ulcerated breast neoplasm is a condition that frequently occurs in developing countries. Generally, it is centrally localized and submitted to neoadjuvant therapy; thereafter, upon disappearance of the ulceration, it is submitted to radical mastectomy. Presence of axillary infiltration and ulceration with incomplete response makes it necessary for the use of surgical flaps for skin closure. We report a case in which primary reconstructive surgical procedure and skin closure was necessary, where we used double myocutaneous flaps-the latissimus dorsi and VRAM (vertical rectus abdominis myocutaneous) flap. We discussed treatment of the ulcerated lesions, possible surgical solutions, and the conditions associated with the use of double flaps. For primary closure of extensive areas, double myocutaneous flaps can be used as a solution in cases where skin grafts or surgical microsurgical flaps are not able to serve as a surgical solution. Myocutaneous flaps are associated with lower rates of complication, allowing for rapid recovery without increasing the time necessary before the next adjuvant therapy.